Case Report: Diagnostic challenges in Fabry disease: misinterpreted obstructive hypertrophic cardiomyopathy and the role of enzyme replacement therapy - Cheng, Weili; Ao, Mingqiang; Xu, Dinghu; Zhang, Yuqing; Tao, Qin (Frontiers in Cardiovascular Medicine, 2024)
Fabry disease (FD) is a rare X-linked inherited lysosomal storage disorder. The abnormal accumulation of metabolic substrates induces inflammation and fibrosis in cells, resulting in organ dysfunction. The clinical manifestations of FD are diverse and non-specific. In the present study, we report a case initially treated as obstructive hypertrophic cardiomyopathy for several years, which was finally identified as FD through whole-exome sequencing (WES). The patient, diagnosed with obstructive hypertrophic cardiomyopathy, underwent left ventricular outflow tract surgery before visiting our hospital. WES was proposed by our cardiomyopathy center and, unexpectedly, a mutation [c.595T>C (p.Val199Met)] in exon 4 of the GLA gene was identified. A subsequent analysis of plasma α-galactosidase and globotriaosylsphingosine levels confirmed the diagnosis of FD. Although enzyme replacement therapy (ERT) was initiated immediately after diagnosis, the patient experienced aortic valve damage and left heart enlargement 2 years later. Subsequently, the patient underwent transcatheter aortic valve replacement. This case implies that FD should be considered a potential cause in patients with unexplained left ventricular hypertrophy. Delayed initiation of ERT may compromise its efficacy.